Clinical Findings in a Pati ent with Large B-Cell Lymphoma andNeuroniti s: A Case Study - Smith, Kaylee J.; Angster, Kristen; Arbogast, Taylor; Cheema, Atif (Journal of the American Academy of Audiology, 2023)
Background Given the multifaceted nature of the balance system, an interdisciplinary approach to patient care is imperative. For surgical patients with complex medical histories, comprehensive vestibular evaluations provide information on baseline vestibular function and identify possible surgical risks and outcomes. This case study follows a patient diagnosed with probable right vestibular neuronitis immediately preceding surgical resection of a left brainstem lesion, later diagnosed as a B cell lymphoma (BCL) and provides details regarding pre- and postsurgical outcomes.Purpose This case study expands on the importance of the inclusion of vestibular audiologists on the interdisciplinary team for related surgical procedures to provide insight into possible surgical risks and subsequent effects on patients' postsurgical quality of life.Research Design Case report.Study Sample A 68-year-old female patient evaluated within the Henry Ford Health System for management of diffuse large BCL.Data Collection Standard neuro-otology, neuro-surgical, audiological, and vestibular evaluations were conducted to evaluate the patient's complex symptomology.Results This case report outlines a patient hospitalized for a left brainstem mass, later diagnosed as an aggressive form of lymphoma, with a concurrent episode of vestibular neuronitis on the contralesional side. Functional outcomes are discussed following surgical intervention to remove the mass. Postsurgical vestibular testing revealed a bilateral vestibular hypofunction.Conclusions Vestibular audiology plays an essential role in the multidisciplinary team for complex dizzy patients with related surgical procedures, as this subset of the field can offer critical insight into postsurgical recommendations and patient expectations.
Keywords: dizziness; non-Hodgkin lymphoma; vestibular neuronitis